Selection of technological solutions in the construction and reconstruction of wastewater treatment facilities in settlements - Dubianok, Sniazhana; Akhmadziyeva, Yulia (Journal of the Belarusian State University. Ecology, 2023)
Wastewater treatment plants of settlements in the Republic of Belarus, taking into account the existing scheme of sewerage of settlements in the country, carry out wastewater treatment from the population, social facilities and industrial facilities. At the same time, the vast majority of treatment facilities in settlements were built in the period 1970–1990 of the last century and need to be reconstructed both in terms of power changes and in terms of the use of more modern technologies for wastewater treatment and treatment of sludge that forms during the operation of treatment facilities. There are no unified strategic approaches to the choice of technology for wastewater treatment and sludge treatment for enterprises operating wastewater treatment plants in settlements in the Republic of Belarus. The analysis of the national legislation in the field of the use and protection of water resources and the management of water management systems, as well as the analysis of the functioning of wastewater treatment plants in settlements, made it possible to determine the technological parameters of the operation of wastewater treatment facilities in settlements, suitable as criteria for a comprehensive assessment of technological solutions during construction, reconstruction wastewater treatment plants of settlements.